Pengaruh Content Marketing, Customer Satisfaction dan Customer Trust terhadap Customer Retention Dengan Customer Value Sebagai Variabel Moderasi: - Puspitaloka, Tamara Lisna; Nurhadi, Nurhadi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of content marketing, customer satisfaction and customer trust on customer retention with customer value as a moderating variable. The population of this research is McDonalds generation z customers in Surabaya. Sampling was obtained using a non-purposive sampling method with a total sample of 100 obtained from the calculation of the unknown population formula. This study uses a quantitative approach with data obtained through distributing questionnaires and processed by multiple linear regression analysis and Moderated Regression Analysis test. The results of the study show that content marketing has a positive and not significant effect on customer retention while customer satisfaction and customer trust have a positive and significant effect on customer retention. Then for the Moderated Regression Analysis test results provide evidence that customer value moderates the effect of customer satisfaction on customer retention but customer value does not moderate the effect of content marking and customer trust on customer retention. Keywords: Customer Retention; Content Marketing; Customer Satisfaction; Customer Trust; Customer Value